Integrating network toxicology, transcriptomics, and metabolomics uncovers the hepatotoxic mechanisms of okadaic acid in LO2 cells - Zhiqiang Luo; Fulu Pan; Huixia Fan; Ruofan Guo; Jingqi Zheng; Shuo Zhang; Jiaru Shi; Wei Lin; Chen Wang; Yanli Pan; Guohua Yu (Ecotoxicology and Environmental Safety, 2025)
Okadaic acid (OKA), a potent phycotoxin existed in shellfish, is known to cause liver damage. However, the hepatic mechanisms underlying its toxicity remain poorly understood. In this work, we aim to elucidate the hepatotoxic mechanisms of OKA by integrating network toxicology with transcriptomic and metabolomic analyses. The results showed that OKA induced hepatotoxicity through cell cycle arrest and apoptosis in LO2 cells. Both network toxicology and transcriptomic analyses identified the MAPK signaling pathway as highly enriched. Key genes involved in the MAPK pathway, including MAP2K3, MAP3K14, MAP3K8, TNF, IL1A and NFKB2, were validated by qPCR and found to be upregulated. Western blot analysis further revealed that OKA significantly upregulated p-p38 expression, with no significant effect on p-ERK and p-JNK levels. Treatment of LO2 cells with the p38 inhibitor SB203580 mitigated OKA-induced hepatotoxicity, supporting the critical role of p38 MAPK signaling in OKA-mediated hepatotoxicity. Additionally, metabolomic data demonstrated that OKA primarily disrupted metabolic pathways, including cysteine and methionine metabolism, glutathione metabolism, and lipolysis regulation. Further integration of transcriptomics and metabolomics revealed that OKA caused metabolic dysfunction by altering vital metabolites, including diisooctyl phthalate, gamma-glutamylglutamate, and gamma-glutamylglutamine. In summary, these findings provide valuable insights into the mechanisms underlying OKA-induced hepatotoxicity, emphasizing the integration of network toxicology, transcriptomics, and metabolomics as a novel strategy for studying the action modes of biotoxins.